Deiksis Dalam Novel Aku Bulan Kamu Senja Karya Syafruddin Pernyata: Kajian Pragmatik - Safitri, Yuliana; Hudiyono, Yusak; Sulistyowati, Endang Dwi (Adjektiva: Educational Languages and Literature Studies, 2021)
The purpose of this study is to describe the forms and types of deixis and the function of deixis reference contained in the conversation of the novel Aku Bulan Kamu Senja by Syafruddin Pernyata. This study uses a qualitative descriptive method with content analysis data processing. The data source in this study comes from the novel Aku Bulan Kamu Senja by Syafruddin Pernyata. The data collection technique used is the listening technique and the note-taking technique with the use of research instruments, namely data cards. The results showed that there are three forms of deixis in the novel Aku Bulan Kamu Senja by Syafruddin Pernyata, namely (1) morpheme deixis, (2) word deixis, and (3) phrase deixis, and five types of deixis, namely (1) deixis persona which is divided into three parts, namely (a) first person deixis plural and singular, (b) second person deixis plural and singular, and (c) third person deixis plural and singular, (2) time deixis includes time ( a) the occurrence of the incident, (b) the past, and (c) the future, (3) place deixis includes (a) the close distance to the speaker and speech partner, and b) the long distance from the speaker and speech partner, 4) Social deixis includes (a) language manners, and (5) discourse deixis includes (a) anaphora and (b) cataphora. The reference function of various types of deixis refers to the conversation contained in the novel according to the existing context.